#### Answer

-16

#### Work Step by Step

$3(x+5)=2x-1 \lt=\gt 3x + 15 \lt=\gt 2x-1 \lt=\gt 3x +16 = 2x \lt=\gt x = -16$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

-16

$3(x+5)=2x-1 \lt=\gt 3x + 15 \lt=\gt 2x-1 \lt=\gt 3x +16 = 2x \lt=\gt x = -16$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.